The Role of Political Parties in SBY's Era of Leadership Period 2004-2014 - Ishaq Rahman; Elyta Elyta (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2020)
ABSTRACT A country that implements the system as mentioned earlier is more towards an authoritarian system of government which aims to dominate and dominate the power of the state towards the people. Democracy cannot survive from such a closed state. In a basic concept of democracy, there is a fundamental principle, namely the principle of sovereignty of the people who run the government.Political communication is one of the many roles played by political parties in various available arrangements. The political party is required to communicate knowledge, issues and political thoughts.Constitutionally, the Government adopts a Presidential System in which the ministers in the cabinet are responsible to the president. But in practice the SBY-JK administration is more of a Parliamentary System. Keywords: political parties, democracy, SBY government